Virtual strategy focused on industry 4.0 on an industrial pilot plant (Revista Cientifica Ingenio Magno, 2022)
This work shows how a tool related to industry 4.0 was developed and itsimplementation to be used in teaching-learning processes, especially in the area of industrialautomation of the Faculty of Mechatronics Engineering of the Universidad Santo Tomás -Bucaramanga Seccional Colombia. This tool was made following the methodology ofanalysis, foundation, design and finally an implementation. The tool has been made througha local web page and a mobile application in charge of controlling, storing, generatingreports and issuing data obtained by a Siemens s7-1200 PLC controller, from an instrumentedindustrial pilot plant. The page stores an interface for an initial didactic control, to generatereports from a MySQL database and an interface in charge of monitoring with a supervisionsystem (SCADA). The mobile application runs on Android and has interaction interfacesfor the control and monitoring of information through augmented reality, with which it ispossible to observe the symbols of the elements of an industrial pilot plant and thus selectand issue or receive data from the selected device. In addition, the application allows youto interact to obtain information on each particular element.
Keywords: Industry 4.0, mobile application, web page, virtual instrumentation